Changing the conversation on evaluating digital transformation in healthcare: Insights from an institutional analysis. Issue 1 (March 2020) - Burton-Jones, Andrew; Akhlaghpour, Saeed; Ayre, Stephen; Barde, Payal; Staib, Andrew; Sullivan, Clair
Abstract: The global health sector is engaged in significant digital transformation. Evaluating these transformations is important given the major investments involved and their major potential consequences. However, studies have critiqued both the quality of evaluations and the quality of evaluation research. The persistent lack of progress has led researchers to ask deeper questions about what is actually occurring when teams evaluate the benefits of digital transformation. This translational research essay explores how institutional theory offers a lens for understanding the complexities of evaluating digital transformations in healthcare and provides insights for improving it. In particular, we show how institutional theory can explain behaviors observed in the literature and in our own case study. We also show how institutional theory can benefit from the insights observed in evaluation work. Motivated by these opportunities, we suggest an agenda through which practitioners and researchers can jointly improve work in this area. Highlights: The worldwide healthcare sector is undergoing significant and expensive digital transformations The evaluation of these consequential transformations is important, but, research and practice in this domain are problematic We demonstrate how Institutional Theory provides a useful lens for understanding the evaluation of digital transformation We also show Institutional Theory can benefit from insights learned during evaluations We offer an agenda for future dialogue between academics and practitioners to improve evaluation practice